APPLICATION OF THE SWOT-ANALYSIS IN PROJECT MANAGEMENT IN BUSINESS ORGANIZATIONS - Borislava Galabova (Science & Research, 2019)

(untitled)
In today's environment most business organizations realize a substantial part of its activities on the principle of projects. Project is a complex undertaking with a specific goal. The realization of this goal in a planned period and quality of the final product means that it’s successfully completed. Innovation and changes in business organizations are typically performed through the implementation of projects. In the rapidly changing economic environment the realization of projects, as a working tool for strategic change, is reasonably necessary. For that reason, the report summarizes the opportunities for application of one of the classic methods for strategic planning – the SWOT-analysis, in the project management process. Some benefits from its use are derived, based on a critical review and analysis. Good practices, applicable to business projects, are resumed.